Understanding Fc Receptor Involvement in Inflammatory Diseases: From Mechanisms to New Therapeutic Tools - Ben Mkaddem, Sanae; Benhamou, Marc; Monteiro, Renato C. (Frontiers in Immunology, 2019)
Fc receptors (FcRs) belong to the ITAM-associated receptor family. FcRs control the humoral and innate immunity which are essential for appropriate responses to infections and prevention of chronic inflammation or auto-immune diseases. Following their crosslinking by immune complexes, FcRs play various roles such as modulation of the immune response by released cytokines or of phagocytosis. Here, we review FcR involvement in pathologies leading notably to altered intracellular signaling with functionally relevant consequences to the host, and targeting of Fc receptors as therapeutic approaches. Special emphasis will be given to some FcRs, such as the FcαRI, the FcRIIA and the FcRIIIA, which behave like the ancient god Janus depending on the ITAM motif to inhibit or activate immune responses depending on their targeting by monomeric/dimeric immunoglobulins or by immune complexes. This ITAM duality has been recently defined as inhibitory or activating ITAM (ITAMi or ITAMa) which are controlled by Src family kinases. Involvement of various ITAM-bearing FcRs observed during infectious or autoimmune diseases is associated with allelic variants, changes in ligand binding ability responsible for host defense perturbation. During auto-immune diseases such as rheumatoid arthritis, lupus or immune thrombocytopenia, the autoantibodies and immune complexes lead to inflammation through FcR aggregation. We will discuss the role of FcRs in autoimmune diseases, and focus on novel approaches to target FcRs for resolution of antibody-mediated autoimmunity. We will finally also discuss the down-regulation of FcR functionality as a therapeutic approach for autoimmune diseases.